Assessment of combining ability and heterosis for yield and its component traits in Indian mustard [Brassica juncea (L.) Czern and Coss.]: Assessment of combining ability and heterosis for yield and its component traits in Indian mustard [Brassica juncea (L.) Czern and Coss.] - ROHIT; RAM AVTAR; NEERAJ KUMAR; MANJEET SINGH; SUBHASH CHANDER (Journal of Oilseeds Research, 2023)
Line × tester analysis was carried out to estimate heterosis and combining ability effects of 32 Indian mustard hybrids. Three lines, namely, RH 30-OA, RH 115-OA, and RH 832-OA, as well as two testers, Ogura 17 and Ogura 101 were discovered to be good general combiners with significant positive general combining ability (GCA) effects for seed yield/plant and component traits. Specific combining ability (SCA) effects for seed yield/plant were significantly positive for RH 30-OA × Ogura 101 and RH 832-OA × Ogura 72 crosses which exhibited significant economic heterosis compared to the standard check DMH 1.